Features of the Course of Rheumatoid Arthritis Depending on The C3435t Polymorphism of The Mdr1 Gene - N. Abdurakhmanova; Kh. Akhmedov; S.Rakhimov (Zien Journals, 2023)
examine the MDR1 gene C3435 T polymorphism and it's clinical relevance in rheumatoid arthritis patients. materials and methods. The study was carried out on 76 patients with RA and 24 healthy people. results and discussion. From the results of our study, it follows that the possessor of the CC of the genotype C3435T isoform of the MDR1 gene showed high drug resistance and on the contrary, the possessor of the TT genotype showed a high drug response and a longer remission. The MDR1 gene C3435T polymorphism may have a certain effect on the course and efficiency of treatment rheumatoid arthritis.
Keywords: MDR1; C3435T; rheumatoid arthritis; genotype